Development and validation of a core endurance intervention program: Implications for performance in college-age rowers - Tse, M. A.; McManus, A. M.; Masters, R. S. W. (The Journal of Strength and Conditioning Research, 2005)
The objective of this study was to examine the effectiveness of a core endurance exercise protocol. Forty-five college-age rowers (age 21 +/- 1.0) were assigned to either a core training group [core group] (n = 25), which took part in a core endurance intervention exercise protocol, or to a control training group [control group] (n = 20), which was not given any specialized core training. Training took place 2 days per week for 8 weeks. Trunk endurance was assessed using flexion, extension, and side flexion tests, whereas a variety of functional performance measures were assessed (vertical jump, broad jump, shuttle run, 40-m sprint, overhead medicine ball throw, 2,000-m maximal rowing ergometer test). The results revealed significant improvement in the two side flexion tests for the core group (p < 0.05). Interestingly, significant differences were noted in the trunk extension test endurance times for the control group (p < 0.05), but not for the core group. No significant differences were found for any of the functional performance tests. In summary, the 8-week core endurance training program improved selected core endurance parameters in healthy young men, but the effectiveness of the core intervention on various functional performance aspects was not supported.